UV-cured Al2O3-laden cellulose reinforced polymer electrolyte membranes for Li-based batteries. (20th January 2015) - Chiappone, A.; Nair, J.R.; Gerbaldi, C.; Bongiovanni, R.; Zeno, E.
Abstract: A methacrylate based plasticised polymer electrolyte membrane is prepared via a rapid and facile UV curing process, the major concerns of mechanical integrity are overcome by simply using appropriately modified cellulose handsheet laden with nano-sized acidic alumina particles as a reinforcement. The use of the cellulose handsheets greatly enhances the flexibility and mechanical properties of the membrane while the addition of alumina particles helps to maintain satisfactory conductivity values. The reinforced composite electrolyte membrane is also tested in a real lithium cell, exhibiting excellent performance which account for its use in futuristic lithium batteries having low cost, environmentally friendly and easily scalable properties.